Preoperative Evaluation in Patients With End-Stage Renal Disease and Chronic Kidney Disease - Rabih Nasr; Sridhar Chilimuri (SAGE Publishing, 2017)
Optimal preoperative management of dialysis patients remains challenging. Patients with end-stage renal disease (ESRD) have higher mortality in the perioperative setting compared with non-ESRD patients. However, it is well established that dialysis should be done on the day before surgery. Additional dialysis session prior to surgery does not improve outcomes. All dialysis patients should undergo blood work to check electrolytes and especially serum potassium prior to any surgery. Some medications, including angiotensin-converting enzyme inhibitors, angiotensin receptor blockers, and diuretics, should be stopped prior to surgery to minimize hemodynamic changes during surgery. The dialysis access should be carefully examined for any signs of infection. The arteriovenous fistula or graft should be evaluated for patency. Glycemic control in diabetic ESRD and chronic kidney disease patients is very important, and clinicians should be aware of the risk of bleeding and the appropriate analgesics that can be used in dialysis patients in the perioperative setting. In conclusion, preoperative evaluation in patients with ESRD should be a multidisciplinary approach.